A noção de felicidade em Teilhard de Chardin um estudo a partir de suas obras: O meio divino e Sobre a felicidade/ sobre o amor - Lucarelli, Vera Lucia Moreira Alves (2023)
The research attempts to delimit how the socio-historical context of Teilhard de Chardin, and the influences received contributed to his scientific-spiritual trajectory and to the construction of his thought. For the study of the notion of happiness in this author, two of his works were chosen: The Divine Milieu and About Happiness/About Love. However, to understand other aspects of the author's thought, the other of your works and other authors were consulted who contributed with valuable information about his quest to build an ideal of science, love, and spirituality, which enshrines him before his own feelings in his lonely days in the Chinese deserts. His years spent in exile were fundamental in discovering his mystical path. His religious and intellectual trajectory awakened in Teilhard de Chardin a certain sensitivity in relation to the evolution of Creation. For Teilhard de Chardin, the idea of the evolution of humanity became more and more his scientific perspective, despite realizing that he would never separate the intellectual from the spiritual, as he saw in Matter, Life and Energy, the pillars of his concerns and dearest joys. He saw no conflict between faith and science when it comes to the "heart of the Matter". Teilhard de Chardin looked for explaining the man scientifically within the evolution of the world towards a spiritual and divine reality, through the spirit, which is, therefore, human, essential constitutive of man, which is formed by the divine power that is the love that moves towards infinity. For the author, it is the human person who can give meaning to the history of the world in search of happiness